RF Energy Harvesting and Wireless Power Transfer for IoT - Onel Luis Alcaraz López; Katsuya Suto (Sensors)
The rapid proliferation of the Internet of Things (IoT) has transformed modern living by interconnecting billions of devices across industrial, commercial, and domestic sectors [...]